IMPLEMENTASI GOOGLE CLASSROOM TERINTEGRASI GOOGLE FORMULIR SEBAGAI MEDIA EVALUASI PEMBELAJARAN MATEMATIKA DASAR - Baharuddin (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2025)
This study aims to describe the implementation of Google Classroom integrated with Google Forms as an evaluation medium in Basic Mathematics learning. The purpose of this study is to improve the effectiveness of the learning evaluation process through the use of digital technology with active student involvement and the efficiency of learning outcome management. This study used a qualitative descriptive approach with 28 students of the Biotechnology study program at Makassar State University as subjects. Data were collected through observation, interviews, and analysis of evaluation documents using Google Forms within the Google Classroom platform. The results show that the integration between Google Classroom and Google Forms creates a more accessible evaluation process. Students demonstrated active participation in evaluations, timely submission of assignments, and an understanding of basic mathematical concepts. In addition, lecturers found it easier to analyze learning outcomes through automatic data generated by Google Forms. The results of this study provide a model for implementing digital evaluation that can be replicated by educators at various levels and subjects. The results of this study also show that the application of learning technology can improve students' digital literacy and strengthen a culture of independent learning.